Cost and Benefit Analysis of Encircling Gill Net Fishery - Waileruny, Welem; Syauta, Franklin; Leskona, Faldo; Kaihena, Yoel (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2025)
The importance of cost and benefit analysis of fishing business is intended to provide information to fishermen about the amount of profit obtained and the potential financial risks that will be faced. The purpose of this study was to determine the amount of costs, income and profit and feasibility of the business. This study was conducted in Waai Village, Salahutu District, Central Maluku Regency. Data collection through interviews and observations and analyzed using cost and benefit analysis and investment criteria. The results of the analysis showed that the total cost each year was IDR 24,211,167 and the total income each year was IDR 42,480,000, so the net profit each year was IDR 18,268,833. From a financial aspect, this business is feasible to develop because it has a positive NPV and net B/C> 1.